2021
DOI: 10.3390/jmse9040379
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Glass Fiber Content and Reinforcement Combination on Pulse-Echo Ultrasonic Measurement of Composite Ship Structures

Abstract: Ship structures made of glass fiber-reinforced polymer (GFRP) composite laminates are considerably thicker than aircraft and automobile structures and more likely to contain voids. The production characteristics of such composite laminates were investigated in this study by ultrasonic nondestructive evaluation (NDE). The laminate samples were produced from E-glass chopped strand mat (CSM) and woven roving (WR) fabrics with different glass fiber contents of 30–70%. Approximately 300 pulse-echo ultrasonic A-scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…For homogeneous materials, including steel, the ultrasonic pulse-echo velocity and impedance for a given material density are available for review [13] and can thus be applied to testing. In a homogeneous material, the ultrasonic propagation speed is constant, and the propagation characteristics are consistent.…”
Section: Ultrasonic Testing Of Composite Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…For homogeneous materials, including steel, the ultrasonic pulse-echo velocity and impedance for a given material density are available for review [13] and can thus be applied to testing. In a homogeneous material, the ultrasonic propagation speed is constant, and the propagation characteristics are consistent.…”
Section: Ultrasonic Testing Of Composite Materialsmentioning
confidence: 99%
“…In previous studies conducted by Stone and Clarke [23], Ishii et al [24], and Lin et al [25], voids were confirmed to disrupt the propagation of ultrasonic waves and increase scattering and absorption. In addition, Lee et al [13] observed that a void content of 5% in GFRP hull plates considerably reduced the ultrasonic pulseecho velocity. With an increase in the Gc of plates, there is an increase in the probability of defect formation, i.e., voids [13,26], and these defects lead to the disruption of ultrasonic wave propagation.…”
Section: Ultrasonic Testing Of Composite Materialsmentioning
confidence: 99%
See 3 more Smart Citations